A case of intractable Dysmenorrhoea - Shati, Mariam Faruqui; Begum, Nasreen; Jahan, Nasim (Northern International Medical College Journal, 2015)
Dysmenorrhea (dysmenorrhoea or painful periods) is a medical condition of pain during menstruation that interferes with daily activities, defined by ACOG (American Congress of Obstetricians and Gynecologists). Still, dysmenorrhea is often defined simply as menstrual pain or at least menstrual pain that is excessive. A 19yr old girl presented frequent dysmenorrhoea which was increasing in intensity and finally a lump was palpable on the left lower abdomen. She was treated surgically. A big mass size of a cricket ball was removed by laparotomy and patient was relieved from intractable dysmenorrhoea. Northern International Medical College Journal Vol.5(2) 2014: 351-352